Investigation of exogenous GnRH and opioid antagonists, alone and in combination, on gonadotropin and ovulatory responses in transitional mares under various progesterone environments - Stafford, Erika; Sinclair, Chelsea; Stevenson, Jeff; Grady, Jason; Kouba, Joann M. (My University, 2017)
During the spring between anestrous and the resumption of normal cyclicity, mares experience a transitional period characterized by increasing hormone concentrations and follicular development, along with the resumption of estrus behavior. Endogenous opioids have been observed to suppress GnRH in mares and therefore may play a role during anestrous and during this transitional period. Opioid antagonists and GnRH agonists have been previously used to induce mares to ovulate at the end or following the transitional period, but never in combination. This study examined transitional mares and their response to 1 of 3 treatments, as well as the conception rates after the first ovulation, with the hope to decrease time to the first ovulation and improve conception rates. Eighteen transitional mares were separated into 3 groups of 6 mares. One group received the opioid antagonist naloxone (0.5 mg/kg BW), the next received the GnRH agonist deslorelin (1 mL), and the final group received naloxone first followed by deslorelin 1 hour later. Mares in all treatment groups were first primed with exogenous progesterone (Regu-Mate) for 14 days, with blood samples collected on the 14th day of Regu-Mate treatment. This collection period represents Phase 1. Sampling for Phase 2 occurred when the mares had a follicle greater than 35mm following the cessation of Regu-Mate. Following sampling for Phase 2, all mares were bred to the same stallion the next day. Seven days post-ovulation, when endogenous progesterone was high, sampling for Phase 3 occurred, followed by a pregnancy check 14 days post-ovulation. During each phase, blood was drawn every 15 minutes from the mares, including an hour of pre-treatment baseline samples and 5 hours of post-treatment sampling. The plasma was harvested and frozen and will be analyzed for LH, FSH, and progesterone. The hypothesis is that the group receiving both treatments will have the highest LH and FSH levels, particularly at times of high progesterone levels (Phase 1 and 3). It is also theorized that this group will have a higher conception rate than the groups receiving either naloxone or deslorelin alone. Although all mares have yet to complete all phases and pregnancy checks, so far, the group receiving both treatments had fewer days on average between Phase 1 and 2 at 7 days, compared to 11.8 and 11.5 days for the naloxone and deslorelin groups respectively. The time between Phase 2 and ovulation is also shorter for the combination treatment group at an average of 3.5 days, compared to 4.4 and 6 days for the naloxone and deslorelin groups respectively.
Keywords: Spring 2017